Hyperbaric oxygen potentiates platelet-rich plasma composition and accelerates bone healing - Wen-Shuo Chang; Chien-Cheng Huang; Tzu-Hao Chen; Ssu-Han Chao; Cheng-Hsien Lin; Ching-Ping Chang; Chi-Sheng Chien (Journal of Orthopaedic Translation)
Objective: This study aimed to investigate whether platelet-rich plasma (PRP) obtained from the blood of rats preconditioned with hyperbaric oxygen (HBOP) would enhance the biological activity of PRP and accelerate the healing process of femur fractures in a rat model. Design: PRP was derived from blood samples of healthy rats subjected to either hyperbaric oxygen (hPRP) or normobaric air (nPRP). A closed femur fracture model was established in male Wistar rats, with treatments of hPRP or nPRP administered around the fracture site immediately post-fracture and on days 7, 14, 21, and 28. Growth factor concentrations in hPRP and nPRP were biochemically quantified. Bone healing was assessed weekly by X-ray, while histological and immunofluorescence analyses evaluated inflammatory status, osteoprotegerin (OPG), receptor activator of nuclear factor kappa-B ligand (RANKL) expression, and the presence of osteoblasts, osteoclasts, and osteocytes during healing. The effects of hPRP and nPRP on MC3T3-E1 preosteoblast migration and proliferation were also tested in vitro. Results: hPRP showed significantly higher concentrations of growth factors such as activin-A, brain-derived neurotrophic factor, nerve growth factor, Flt-3 Ligand, granulocyte-macrophage colony-stimulating factor, hepatocyte growth factor, and platelet-derived growth factor, compared to nPRP. In vitro, hPRP demonstrated more significant effects on preosteoblast migration and proliferation. In vivo, hPRP treatment resulted in enhanced bone healing, higher OPG levels in osteoblasts and osteoclasts, and an elevated OPG/RANKL ratio compared to nPRP. Conclusions: HBOP enhances the biological activity of PRP and accelerates bone healing in a closed femur fracture model in rats. This study highlights the regenerative potential of PRP when preconditioned with hyperbaric oxygen for use in bone fracture therapy. Significance statement: PRP is widely used in treating bone defects and fractures, but its enhancement through HBOP remains underexplored. Our findings demonstrate that HBOP potentiates the biological activity of PRP, offering promising therapeutic potential for bone fracture healing. The translational potential of this article: Enriching growth factors in PRP through HBOP could significantly improve tissue regeneration, especially in bone healing. The potential of hPRP in clinical applications is highly promising, particularly in orthopaedic surgery, trauma care, sports medicine, and managing bone healing in compromised patients.